Cholesterol Peroxidation as a Special Type of Lipid Oxidation in Photodynamic Systems() - Girotti, Albert W. (Photochem Photobiol, 2018)
Like other unsaturated lipids in cell membranes and lipoproteins, cholesterol (Ch) is susceptible to oxidative modification, including photodynamic oxidation. There is a sustained interest in the pathogenic properties of Ch oxides such as those generated by photooxidation. Singlet oxygen ((1)O(2))-mediated Ch photooxidation (Type II mechanism) gives rise to three hydroperoxide (ChOOH) isomers: 5α-OOH, 6α-OOH, and 6β-OOH, the 5α-OOH yield far exceeding that of the others. 5α-OOH detection is relatively straightforward and serves as a definitive indicator of (1)O(2) involvement in a reaction, photochemical or otherwise. Like all lipid hydroperoxides (LOOHs), ChOOHs can disrupt membrane or lipoprotein structure/function on their own, but subsequent light-independent reactions may either intensify or attenuate such effects. Such reactions include (a) one-electron reduction to redox-active free radical intermediates, (b) two-electron reduction to redox-silent alcohols, and (c) translocation to other lipid compartments, where (a) or (b) may take place. In addition to these effects, ChOOHs may act as signaling molecules in reactions that affect cell fates. Although processes a-c have been well studied for ChOOHs, signaling activity is still poorly understood compared with that of hydrogen peroxide. This review focuses on these various aspects Ch photo-peroxidation and its biological consequences.